Analyzing the validity of a DFT-based improved acoustic OFDM transmission along rotating simulated drillstring. (15th December 2016) - Cheng, Li; Jinfeng, Chang; Shangchun, Fan; Jun, Yang
Abstract: In the oil industry, drillstring can be used as a transmission medium to send downhole information via a modulated compressional acoustic wave. However, the accompanied reverberation is a major constraint in the transmission rate and distance because of the multipath fading caused by the heterogeneous drillstring. In combination with discrete Fourier transform-spread (DFT-S) mapping/demapping, high-power amplitude squeezing and DFT-based least squares channel estimation methods, an improved orthogonal frequency division multiplexing (OFDM) scheme is proposed in this paper to overcome the symbol interference inherent in the drillstring multipath channel and reduce the peak-to-average power ratio of the signal. Then an experimental rig is established by using a rotatable electromagnetic vibration exciter and a piezoelectric accelerometer arranged at the position closer to acoustic impedance terminal along a 6.3-m periodic simulated drillstring. The OFDM data sequences at a data rate of 200 bit/s over a limited bandwidth of 140 Hz are applied to the rotating simulated drillstring. The experimental results show that the proposed scheme using QPSK modulation can offer an error-free acoustic communication at rotation speeds up to 90 r/min. Highlights: A DFT-based improved OFDM scheme for rotating fading drillstring channel is proposed. The DFT-based LS channel estimation with high-power amplitude squeezing is modeled. An acoustic transmission experimental rig using a rotatable electromagnetic exciter is developed. Improved acoustic transmission performance of OFDM signal is validated by experiment. The scheme can offer an error-free acoustic communication at rotation speeds up to 90 r/min.